Evaluation of changes of indicators characterizing the results of labour market policy - Okunevičiūtė Neverauskienė, Laima; Pocius, Arūnas (Lithuanian Journal of Statistics, 2020)
The main labour market indicators presented in the Employment Enhancement Programme for 2014-20 are evaluated in the article. On the basis of these indicators the situation in the labour market are analyzed; changes from foreseen indicators values (presented in the Employment Enhancement Programme) are evaluated; recommendations for improving the situation are provided. One of the essentials priorities of this article – the evaluation of target groups integration opportunities characterized by labour market policy indicators. Considering/Acoording to the system of labour market indicators presented in the Employment Enhancement Programme which mainly oriented to workplace change (creation), priority is given to employment indicators. The article analyzed the statistical data characterizing the results of labour market policy as well as the additionally indicators describing the target groups situation in the labour market.